﻿Comparison of treatment of COVID-19 with inhaled bromhexine, higher doses of colchicine and hymecromone with WHO-recommended paxlovid, molnupiravir, remdesivir, anti-IL-6 receptor antibodies and baricitinib - Vanyo Mitev (Pharmacia, 2023)
Millions of publications and thousands of clinical trials have not led to the discovery of an effective treatment for COVID-19. We believe that the reason for this is the inaccurate strategy of inhibiting target molecules involved in the pathogenesis of the disease. The leading cause of death in COVID-19 is the cytokine storm, which is caused by an NLRP3 inflammasome hyperreaction. WHO recommends for the outpatients treatment drugs blocking the replication of SARS-CoV-2. However, viral load and replication are not directly related to NLRP3 inflammasome hyperreactivity. This also explains the partial success of the WHO favorite paxlovid to reduce hospitalizations (51%). For hospital treatment, WHO suggests antibodies against the interleukin-6 receptor and Janus kinase (JAK) inhibition. Although important, IL-6 is one of dozens of cytokines elevated as a consequence of cytokine storm. The JAK inhibitor baricitinib inhibited the effect of not only IL-6 but also other elevated cytokines. But if the NLRP3 inflammasome is inhibited, the cytokines will not be elevated, and there will be no need for baricitinib. All medicines recommended by the WHO are distinguished by their very high prices. Our therapeutic strategy is based on inhibition of SARS-CoV-2 entry into the cell and inhibition of the NLRP3 inflammasome. We offer two readily available, cheap and well-known medications - bromhexine hydrochloride and colchicine. The many studies on the treatment of COVID-19 so far have not produced the expected result. The devil is buried in the details. For bromhexine, the reason is the way and its late application. Bromhexine is most effective when given prophylactically or started by inhalation after contact with a person with COVID-19. Its earliest possible application is crucial for its effect. Increased doses of colchicine are necessary for COVID-19 treatment due to the fact that it accumulates in leukocytes, and this leads to inhibition of NLRP3. The high doses we administer have been given widely in the past and are completely safe. Our highest dose is about 5 times lower per kg of weight than the lowest severe toxic dose of colchicine described. Our results show about a 5-fold decrease in hospital mortality and almost complete prevention of hospitalizations if outpatients are treated with inhaled bromhexine and colchicine.